BREEDING AND ITS SELECTION IN BEEKEEPING. - R. Q. Jamolov; R.R.Nabiev; R.O.Azizov (Scholar Express Journal, 2024)
In the article, selection in beekeeping is one of the independent factors of heredity work, which ends with grouping and exclusion from the family in breeding and commodity farms, as well as in beekeeping colonies. Also, phenotypic mass selection - this mass selection is mainly aimed at improving the zoning issues of bees. Individual genotypic selection or selection by origin (estimation). The essence of this type of selection is that, using any highperformance family for future breeding, information is provided to obtain a single indicator that is useful for this particular farm
Keywords: selection; phenotypic; single; heredity